MONTE-CARLO FORECASTING OF LIQUIDITY UNDER UNCERTAINTY - P. Timoshenko (Вестник университета, 2016)
Liquidity planning or forecasting is a complex, complicated by uncertainty and a large number of unknown parameters task. Economical agents solve this problem using various methods and processes to manage liquidity. The article describes a liquidity forecasting process, use of financial modelling, and a method to forecast company’s liquidity via Monte-Carlo modelling.